2021
DOI: 10.1007/s11191-021-00234-x
|View full text |Cite
|
Sign up to set email alerts
|

Shift From a Traditional to a Distance Learning Environment during the COVID-19 Pandemic

Abstract: The paper reports a study aimed at investigating tertiary education students’ engagement and interactions in the traditional face-to-face learning environment and the sequentially applied distance online learning environment imposed by the sudden upsurge of a worldwide health emergency, the COVID-19 pandemic in Spring 2020. The study took place in four distinct science learning communities formed by a total of 347 undergraduate students attending three different academic majors (Chemistry, Environmental Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 54 publications
(57 reference statements)
0
48
1
7
Order By: Relevance
“…Previous studies have also examined the influence of playback speed on the learning effect (Pastore, 2010 ; Ritzhaupt et al, 2015 ). However, contrary to the findings of previous studies, the learning modes have been found to negatively change during the COVID-19 pandemic period (Salta et al, 2021 ). However, students are forced to adopt such unfamiliar method of learning online, which takes a lot of time and energy for them to get used to (Jin et al, 2021 ; Lin et al, 2021 ).…”
Section: Introductioncontrasting
confidence: 98%
“…Previous studies have also examined the influence of playback speed on the learning effect (Pastore, 2010 ; Ritzhaupt et al, 2015 ). However, contrary to the findings of previous studies, the learning modes have been found to negatively change during the COVID-19 pandemic period (Salta et al, 2021 ). However, students are forced to adopt such unfamiliar method of learning online, which takes a lot of time and energy for them to get used to (Jin et al, 2021 ; Lin et al, 2021 ).…”
Section: Introductioncontrasting
confidence: 98%
“…When instructors use interactive technology consistently and purposefully, students feel more connected to the instructor and their peers in an online course [ 39 ]. It is worth stating that the sudden shift in campus education from traditional face-to-face education to an online learning environment has also created challenges for higher education.…”
Section: The State Of the Artmentioning
confidence: 99%
“…Recently, various web-based free accessed platforms have been used to continue education ( Ali, Ramay, & Shahzad, 2011 ; Keskin & Yurdugül, 2020 ; Salta, Paschalidou, Tsetseri, & Koulougliotis, 2021 ). This virtual learning-enabled communication is convenient, especially for introverts ( Salta et al , 2021 ; Walker, Rossi, Anastasi, Gray-Ganter, & Tennent, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various web-based free accessed platforms have been used to continue education ( Ali, Ramay, & Shahzad, 2011 ; Keskin & Yurdugül, 2020 ; Salta, Paschalidou, Tsetseri, & Koulougliotis, 2021 ). This virtual learning-enabled communication is convenient, especially for introverts ( Salta et al , 2021 ; Walker, Rossi, Anastasi, Gray-Ganter, & Tennent, 2016 ). Nevertheless, obstacles remain in technological dilemmas, poor internet providers and limited adaptability, creating hurdles for the students ( Al-Amin et al , 2021 ; Katz, Jordan, & Ognyanova, 2021 ; Shaukat, Niazi, Qazi, & Basit, 2021 ).…”
Section: Introductionmentioning
confidence: 99%